UBS AG : the cost of failing to manage operational risk - Oji, Chijioke; Makin, Viola, 1952- ([London] : SAGE, 2016)
On 15 September 2011, news of United Bank of Switzerland's (UBS) operational failures in its investment banking division hit the market. Kweku Adoboli, a trader who worked at UBS's central London branch, had beaten the control system and carried out a number of unauthorised trades. The trades cost UBS 2.3 billion U.S. dollars in losses - the biggest trading-related loss in the history of banking in Britain, with the impact felt across banks in Europe. Engulfed by calls for closer scrutiny of its entire operational system and trading culture, senior management at UBS fought hard to restore confidence in the bank.
Originally Published in: Oji, C., & Makin, V. (2013). UBS AG: The Cost of Failing to Manage Operational Risk. WBS-2013-3. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; United Bank of Switzerland; Banks and banking, International -- Corrupt practices -- Case studies; Risk management -- Case studies; Bank management -- Case studies